2020
DOI: 10.1039/c9ob02689d
|View full text |Cite
|
Sign up to set email alerts
|

CuBr2-catalyzed diastereoselective allylation: total synthesis of decytospolides A and B and their C6-epimers

Abstract: An efficient, cost effective and protecting group tolerant CuBr2-catalyzed synthesis of 2,6-trans-disubstituted tetrahydropyran with excellent diastereoselectivity, demonstrated in the total synthesis of decytospolides A and B and their C6-epimers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…In recent times the Wittig reaction was used to obtain the chromone‐type compounds. Several synthetic derivatives can be obtained through one‐pot procedures or a more singular one that use β‐cyclodextrin as catalyst . The synthesis of 1 H ‐isochromene derivatives 128 (Scheme ) can be highlighted due to the excellent yields reported for the intramolecular Wittig reaction, but also due to the vast reaction scope reported that is noteworthy.…”
Section: Synthesis Of Analogues Of Natural Heterocyclic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent times the Wittig reaction was used to obtain the chromone‐type compounds. Several synthetic derivatives can be obtained through one‐pot procedures or a more singular one that use β‐cyclodextrin as catalyst . The synthesis of 1 H ‐isochromene derivatives 128 (Scheme ) can be highlighted due to the excellent yields reported for the intramolecular Wittig reaction, but also due to the vast reaction scope reported that is noteworthy.…”
Section: Synthesis Of Analogues Of Natural Heterocyclic Compoundsmentioning
confidence: 99%
“…The synthesis of 1 H ‐isochromene derivatives 128 (Scheme ) can be highlighted due to the excellent yields reported for the intramolecular Wittig reaction, but also due to the vast reaction scope reported that is noteworthy. [96b]…”
Section: Synthesis Of Analogues Of Natural Heterocyclic Compoundsmentioning
confidence: 99%
“…Additionally, transition metal (Cu, Au etc . )-catalyzed hemiacetals or hemiketals can achieve the α-allylation of oxygen-containing heterocyclic compounds 7 (Scheme 1B, strategy 2). Alternatively, cyclization can also proceed under basic or acidic conditions 8 to provide substituted THPs by utilizing prefabricated substrates (Scheme 1B, strategy 3).…”
mentioning
confidence: 99%